1969
DOI: 10.52206/jsmc.2021.11.4.683
|View full text |Cite
|
Sign up to set email alerts
|

To Compare the Effectiveness of Transurethral Pneumatic Lithotripsy and Extracorporeal Shock Wave Lithotripsy: In treatment of Lower Ureteric Stones

Abstract: Background: One of the most common complaint in the ER is colic due to Ureteric calculi. They usually pass out but stones > 5mmmay require intervention. ESWL and TPL are one of the treatment options.Objectives: To compare the effectiveness of transurethral pneumatic lithotripsy (TPL) and extracorporeal shock wavelithotripsy(ESWL) in treatment of lower ureteric stones.Material and Methods: Over period of six months a group of 70 patients presenting with ureteric calculi were randomly allocated intwo groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…There were 677 ESWL patients and 832 URSL patients and the two procedures were analyzed to determine the effect of these two procedures on treatment outcomes. Of the final ten studies, five took place in Pakistan, 1 , 2 , 5 , 17 , 18 , 19 two in Nepal, 4 , 20 one in Japan, 21 and two in Egypt. 22 , 23 All of the studies reported the outcomes of both ESWL and URS lithotripsy procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 677 ESWL patients and 832 URSL patients and the two procedures were analyzed to determine the effect of these two procedures on treatment outcomes. Of the final ten studies, five took place in Pakistan, 1 , 2 , 5 , 17 , 18 , 19 two in Nepal, 4 , 20 one in Japan, 21 and two in Egypt. 22 , 23 All of the studies reported the outcomes of both ESWL and URS lithotripsy procedures.…”
Section: Resultsmentioning
confidence: 99%
“…When medical treatments fail, the two most commonly reported replacement treatments are Extracorporeal Shock Wave Lithotripsy (ESWL) and Ureteroscopic Lithotripsy (URSL) which are performed with rigid-flexible and semi-flexible lithotripters. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%